Effect of Fermentation Duration on the Chemical Characteristics and Antioxidant Activity of Sambiloto Leaf (Andrographis paniculata) Kombucha - Purwono, Tri Diansy Yana; Agustini, Rudiana (Jurnal Pijar Mipa, 2025)
Fermentation is a biotechnological process that can modify chemical characteristics and increase antioxidant activity. The effect of fermentation time is very important for the quality of Andrographis paniculata (Andrographis paniculata) kombucha. This study aims to investigate the potential of sambiloto leaves (Andrographis paniculata) as a base ingredient in kombucha production and to analyze the effect of varying fermentation durations (0, 3, 6, 9, and 12 days) on the chemical characteristics and antioxidant activity of the resulting kombucha. The parameters evaluated include pH, total titratable acidity, total reducing sugars, total flavonoid content, and antioxidant activity. The results showed that the pH of kombucha decreased with increasing fermentation time, from 3,92 ± 0,02 on day 0 to 3.08 ± 0.01 on day 12, indicating enhanced activity of acetic acid-producing microorganisms during fermentation. Titratable acidity increased from 0.11 ± 0.01% to 0.93 ± 0.02%, reflecting the accumulation of organic acids. Total reducing sugar levels initially increased on day 3 (655.72 ± 0.68 mg/mL), then declined to 309.94 ± 0.83 mg/mL by day 12, possibly due to microbial consumption. The total flavonoid content showed a consistent increase from 0.008 mg/mL QE to 0.019 mg/mL QE, indicating the gradual release of bioactive compounds throughout the fermentation process. The highest antioxidant activity was recorded on day 9 (74 ± 0.47%), followed by a slight decrease on day 12 (72 ± 0.00%). These findings suggest that the inclusion of sambiloto leaves does not inhibit fermentation but rather enhances the production of beneficial bioactive compounds. Therefore, sambiloto holds strong potential as a functional ingredient in kombucha rich in natural antioxidants.